Antioxidant activity of phosphatidyl derivatives of hydroxytyrosol in edible oils. Issue 8 (8th May 2014) - Martin, Diana; Garcia‐Serrano, Alba; Casado, Víctor; Vázquez, Luis; Reglero, Guillermo; Torres, Carlos F.
<x xml:space="preserve">Abstract</x> A comparative study of the antioxidant activity of hydroxytyrosol (HT) and phosphatidyl derivatives of hydroxytyrosol (PHT) added at increasing concentrations to diverse edible oils (lard oil, refined olive oil, and diacylglycerol‐rich oil) was performed. Antioxidant activity index was estimated as the ratio of induction time in presence of the compounds to induction time in their absence, after oxidation under Rancimat conditions. Tocopherol (TOC) and phosphatydilcholine (PC) were used as reference, and combinations PHT:TOC, PHT:PC, HT:TOC, and PC:TOC were also tested. PHT and HT showed a protective effect as the added concentration of antioxidants increased. However, the protective effect of PHT was superior to HT for olive oil and diacylglycerol oil, and similar to HT for lard oil. The magnitude of the protection of both PHT and HT was higher in lard oil, followed by olive oil and the poorest protection was for diacylglycerol oil. Both HT and PHT were superior to TOC. Furthermore, PC showed a lack of antioxidant activity compared to PHT. A lack of synergism between the combinations of antioxidants was found. Practical applications: Including phosphatidyl derivatives of hydroxytyrosol in edible oils provides two advantages. First, they serve as a source of hydroxytyrosol and second they stabilize the lipid matrix, and in this respect the phosphatidyl derivatives perform better than hydroxytyrosol or tocopherols. <inline-graphic xlink:href="ark:/27927/pghxt543zh" content-type="ejlt201400053-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> A comparative study of the antioxidant activity of hydroxytyrosol (HT) and phosphatidyl derivatives of HT (PHT) added at increasing concentrations to diverse edible oils (lard oil, refined olive oil, and diacylglycerol‐rich oil) was performed. Tocopherol as reference was also tested. PHT might be included in edible oils with the double strategy to offer a source of HT and, at the same, stabilize the own lipid matrix, even in a superior mode than HT or the standard tocopherol. Nevertheless, the particularity of each individual oil would determine the magnitude of the protection.